2009
DOI: 10.1245/s10434-009-0439-z
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid Tumors of the Anterior Abdominal Wall: Results from a Monocentric Surgical Experience and Review of the Literature

Abstract: Radical resection aided by intraoperative margin evaluation via frozen sections followed by immediate mesh reconstruction is a safe procedure and can provide definitive cure without functional limitations for patients with desmoid tumors of the anterior abdominal wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
5
42
0
3
Order By: Relevance
“…Large defects in anterior abdominal wall as a result of radical resection are managed with immediate mesh reconstruction to minimize functional disability [7].…”
Section: Discussionmentioning
confidence: 99%
“…Large defects in anterior abdominal wall as a result of radical resection are managed with immediate mesh reconstruction to minimize functional disability [7].…”
Section: Discussionmentioning
confidence: 99%
“…[43] привели результаты лече-ния 23 пациентов по аналогичной методике. Некоторые авторы [44][45][46][47] отмечают удовлетворительные функцио-нальные результаты при использовании сетчатых проте-зов из политетрафторэтилена (ePTFE) и целлюлярного дермального матрикса.…”
Section: Discussionunclassified
“…Due to the lack of randomized, controlled trials, we have tried to extrapolate from the published series those cases with tumors localized to the abdominal wall to compare with our findings (2,19,34,110,114,115,137,(182)(183)(184). Table 22.…”
Section: Sporadical Desmoid Tumors Of the Abdominal Wallmentioning
confidence: 94%
“…Many studies have confirmed that 37 to 50% of desmoids arise in the abdominal region, and approximately 10% of all cases are multicentric (7,19,20). Significant differences were detected in the originating between sporadical and hereditary forms.…”
Section: Clinical Presentationmentioning
confidence: 98%
See 1 more Smart Citation